2023
DOI: 10.3390/cells12162113
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Nonthermal Plasma and Tirapazamine as a Novel Combination Therapy to Treat Melanoma In Situ

Matthew Yehl,
Dominik Kucharski,
Michelle Eubank
et al.

Abstract: Although melanoma accounts for only 5.3% of skin cancer, it results in >75% of skin-cancer-related deaths. To avoid disfiguring surgeries on the head and neck associated with surgical excision, there is a clear unmet need for other strategies to selectively remove cutaneous melanoma lesions. Mohs surgery is the current treatment for cutaneous melanoma lesions and squamous and basal cell carcinoma. While Mohs surgery is an effective way to remove melanomas in situ, normal tissue is also excised to achieve hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It was recently shown that specific plasma treatments can be used to convert oncology prodrugs into active pharmaceuticals in vitro [102]. Combinations of either plasma or plasma-activated water with drugs such as Topotecan [103], Tirapazamine [104] or Doxorubicin [105] have been shown to enhance activity in detailed cell culture studies. Dezhpour et al showed that combinations of plasma and doxorubicin were highly effective in reducing tumors in a rodent model study, and that this combination may decrease the dose of chemotherapeutics needed to produce efficacy in a clinical setting [106].…”
Section: Combinations Of Plasma With Traditional Pharmaceuticalsmentioning
confidence: 99%
“…It was recently shown that specific plasma treatments can be used to convert oncology prodrugs into active pharmaceuticals in vitro [102]. Combinations of either plasma or plasma-activated water with drugs such as Topotecan [103], Tirapazamine [104] or Doxorubicin [105] have been shown to enhance activity in detailed cell culture studies. Dezhpour et al showed that combinations of plasma and doxorubicin were highly effective in reducing tumors in a rodent model study, and that this combination may decrease the dose of chemotherapeutics needed to produce efficacy in a clinical setting [106].…”
Section: Combinations Of Plasma With Traditional Pharmaceuticalsmentioning
confidence: 99%
“…It was recently shown that specific plasma treatments can be used to convert oncology prodrugs into active pharmaceuticals in vitro [102]. Combinations of either plasma or plasma-activated water with drugs such as Topotecan [103], Tirapazamine [104] or Doxorubicin [105] have been shown to enhance activity in detailed cell culture studies. Dezhpour et al showed that combinations of plasma and doxorubicin were highly effective in reducing tumors in a rodent model study, and that this combination may decrease the dose of chemotherapeutics needed to produce efficacy in a clinical setting [106].…”
Section: Combinations Of Plasma With Traditional Pharmaceuticalsmentioning
confidence: 99%